Exploration and Characterization of Microorganisms from Rubber Seed and The Benefits for Rubber Plant Growth (Hevea brassiliensis Muell. Arg.) - Dita Amelia Novariza; Lahmuddin Lubis; Suzanna Fitriany Sitepu; Radite Tistama (Jurnal Agroekoteknologi, 2016)
The object of this research are to explore the microorganisms from rubber seed to prevent seed pathogens and beneficial to the growth of rubber plant. The research was conducted in the protection laboratory and greenhouse Sungei Putih Research Center from September to December 2014, using completely randomized design non factorial with 7 treatments and 4 replications. The treatments used are microorganisms exploration of healthy rubber seed, ie M0 (control), M1 (Trichoderma sp.(a)), M2 (Trichoderma sp.(b)), M3 (Aspergillus sp.), M4 (Rhizopus sp.), M5 (Isolates BBK(a)), and M6 (isolates BBK(b)). The results showed that microorganisms exploration from the healthy rubber seed has significant effect on all parameters. The best results to inhibit seed pathogens in the laboratory is Aspergillus sp. at 81.27%. For germinate speed and plants height the best results are Trichoderma sp.(b) at 5.75 days and 28.90 cm. The best results for the length of the root is Trichoderma sp.(a) at 35.10 cm, and for the root weight is Aspergillus sp at 4,91 g. Trichoderma sp.(a), Trichoderma sp.(b), and Aspergillus sp. besides potential as biocontrol agents pathogenic seed by way of seed coating, also has potential as a stimulator of growth and biological fertilizer which can improve the quality of the rubber plant growth. Keywords: rubber plant, antagonistic microorganisms, seed coating, seed pathogens, growth stimulator